I survived : the eruption of Mount St. Helens, 1980 - Tarshis, Lauren (Tarshis, Lauren. I survived, 2016)
On May 18, 1980, eleven-year-old Jessie Marlowe and her best friends, Eddie and Sam, are in a forest near Mount St. Helens when the months of wondering whether the volcano will erupt are finally answered--all three are badly burned, but it is up to Jessie to protect the boys as best she can and hope that somebody comes to rescue them.